Singapore's Baweanese : making sense of a Malay sub-ethnic group identity - Muhammad Afiq Mohd Yusoff (2015)
This paper explores the identity negotiations of the Baweanese in Singapore, one of the many sub-ethnic groups that make up the Malay racial category. The paper shows that race and ethnicity are are very salient sites of identity in the everyday lives of Singaporeans. Yet, the simple CMIO racial categories ignores the internal diversity that exists within each group. The paper looked at how members of the Baweanese community negotiate these complexities and make sense of their sub-ethnic group identities against the competing state-defined ‘Malay’ identity. Using a multi-directional qualitative study, it studied the perspectives of two generations of Baweanese, gen-X and gen-Y, on sub-ethnic group identity, identity construction and markers of identity.